Counselor Education Doctoral Students’ Research Self-Efficacy: A Systemic Perspective - Zahide Sunal; Gulsah Kemer (Teaching and Supervision in Counseling, 2022)
Abstract: Research self-efficacy (RSE) has been mainly considered as an intrapersonal aspect of researcher identity development. Utilizing a systemic lens, we examined factors informing counselor education doctoral students’ RSE in CACREP-accredited doctoral programs. Concept mapping, a mixed-method design, yielded 17 clusters representing six regions describing the factors informing counselor education doctoral students’ RSE. We discussed the results with training and research implications, and limitations. What is the public significance of this article? The present study suggests that there are environmental and relational factors affecting doctoral student’s research self-efficacy (RSE) as well as the previously considered individual factors. Acknowledgement and intentional incorporation of all of these factors may be critical in the counselor education research training process.
Keywords: research self-efficacy; counselor education doctoral students; concept mapping